Book Reviews (Journal of Finance, 1986)
Book reviewed in this article: The Rhetoric of Economics . By DONALD N. MCCLOSKEY. Madison, Wisconsin: University of Wisconsin, 1986. Pp. 224. The Microstructure of Securities Markets . By KALMAN J. COHEN, STEVEN F. MAIER, ROBERT A. SCHWARTZ, and DAVID K. WHITCOMB. Englewood Cliffs, New Jersey: Prentice‐Hall, 1986. Pp. 254. Perspectives on Safe and Sound Banking . By GEORGE J. BENSTON, ROBERT A. EISENBEIS, PAUL M. HORVITZ, EDWARD J. KANE, and GEORGE G. KAUFMAN. Cambridge, Massachusetts: The MIT Press, 1986. Pp. xxi + 358.